Lipidomic Analysis of TRPC1 Ca2+-Permeable Channel-Knock Out Mouse Demonstrates a Vital Role in Placental Tissue Sphingolipid and Triacylglycerol Homeostasis Under Maternal High-Fat Diet - Bukowski, Michael R.; Singh, Brij B.; Roemmich, James N.; Claycombe-Larson, Kate J. (Frontiers in Endocrinology, 2022)
The transient receptor potential canonical channel 1 (TRPC1) is a ubiquitous Ca2+-permeable integral membrane protein present in most tissues, including adipose and placenta, and functionally regulates energetic homeostasis. We demonstrated that elimination of TRPC1 in a mouse model increased body adiposity and limited adipose accumulation under a high fat diet (HFD) even under conditions of exercise. Additionally, intracellular Ca2+ regulates membrane lipid content via the activation of the protein kinase C pathway, which may impact placental membrane lipid content and structure. Based upon this we investigated the effect of HFD and TRPC1 elimination on neutral lipids (triacylglycerol and cholesteryl ester), membrane lipids (phosphatidylcholine and phosphatidylethanolamine), and other multifunctional lipid species (unesterified cholesterol, sphingomyelins, ceramides). The concentration of unesterified cholesterol and sphingomyelin increased with gestational age (E12.5 to E 18.5.) indicating possible increases in plasma membrane fluidity. Diet-dependent increases ceramide concentration at E12.5 suggest a pro-inflammatory role for HFD in early gestation. TRPC1-dependent decreases in cholesterol ester concentration with concomitant increases in long-chain polyunsaturated fatty acid -containing triacylglycerols indicate a disruption of neutral lipid homeostasis that may be tied to Ca2+ regulation. These results align with changes in lipid content observed in studies of preeclamptic human placenta.